Cara Mudah Membuat Portofolio Dan CV Yang Menarik Dan Efektif Dengan Aplikasi Canva Untuk Siswa SMA Negeri 1 Ciseeng - Cahyo Mustiko Bayu; Danu Permana Sukma; Fharadilla Rahmah; Hani Setiani; Ihya Ulumudin; Jepri Naldi; Khurotul Nuraini; Putri Intan Mogot; Rico Aulia Fahreza; Satriya Bagas Eka Saputra; Intan Kumalasari (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In accordance with the title of the community service program, this research aims to improve CV (Curiculum Vitae) that is attractive to Ciseeng 1 Public High School students using the Canva application. The data source comes from Public Relations at Ciseeng 1 Public Vocational High School, namely Mrs. Rahmawati Maela S, Pd. and 36 students of class XII IPS 3. The implementation method used to make a CV & Portfolio is in the form of training using Canva for students of SMK Negeri 1 Ciseeng. This activity is supported by presentations, question and answer sessions and of course hands-on practice in XII IPS 3 class at SMK Negeri 1 Ciseeng. The purpose of implementing this community service program is to expand the network for students, train them to use the knowledge gained at lectures to print blue ink student services in the community. It is hoped that informatics engineering students at Pamulang University will have a strong desire to directly engage in the community as agents of change.